Pharmacoeconomic Analysis of the Use of Omeprazole by Elderly Patients in One of the Primary Healthcare Centers in Brazil - Flavia Cristina Moura Gualberto; Camila Rafaela dos Santos; Cássia Rodrigues Lima Ferreira; Josiane Moreira da Costa (O Mundo da Saúde, 2023)
Omeprazole is the most prescribed proton pump inhibitor in Brazil and is indicated for the treatment of diseases caused by gastroesophageal reflux, peptic ulcer, erosive esophagitis, eradication of Helicobacter pylori, Zollinger-Ellison syndrome, gastrinomas, gastritis, and hypersecretory disorders, as well as peptic ulcer prevention. The indiscriminate and unnecessary use, mainly by the elderly, is an important public health issue to be addressed. Despite the existence of indiscriminate use of omeprazole being known, there is a need to verify how this medication is prescribed in the context of the Unified Health System (UHS) in Brazil. In addition, it is believed that studies that aim to analyze the prescription of omeprazole in a pharmacoeconomic way can contribute to the review or implementation of guidelines and protocols involving the use of this drug. The objective of this study was to characterize and perform a pharmacoeconomic analysis of the use of omeprazole in a Primary Healthcare Centers (PHC) in Minas Gerais, Brazil. This is a descriptive study analyzing the prescriptions of 41 elderly patients treated in the period of April/May 2018 and the following variables were identified: age, sex, dose, indication, endoscopy, other medications in use, and cost of treatment. In the pharmacoeconomic analysis, the average cost of the amount of omeprazole prescribed per patient was calculated and whether or not endoscopy was performed was considered. In the studied population, 29 (70.3%) were female with a median age: 69 years. Only in 4 medical records (9.8%) was there indication for use, and 18 (43.9%) patients had been using omeprazole for more than two years and 7 (17.1%) for more than five years. Only 3 (7.3%) patients underwent endoscopy, and 371 months-worth of omeprazole were used, totaling a financial value of R$35,657.23. The findings suggest long-term prescriptions and no record of their indication on medical records. The cost related to prescriptions could be optimized by performing endoscopy and discontinuing its use when no indication is found.